Deciphering babesia-vector interactions - Antunes, Sandra (2017)
Understanding host-pathogen-tick interactions remains a vitally important issue that might be better understood by basic research focused on each of the dyad interplays. Pathogens gain access to either the vector or host during tick feeding when ticks are confronted with strong hemostatic, inflammatory and immune responses. A prominent example of this is the Babesia spp.-tick-vertebrate host relationship. Babesia spp. are intraerythrocytic apicomplexan organisms spread worldwide, with a complex life cycle. The presence of transovarial transmission in almost all the Babesia species is the main difference between their life cycle and that of other piroplasmida. With more than 100 species described so far, Babesia are the second most commonly found blood parasite of mammals after trypanosomes. The prevalence of Babesia spp. infection is increasing worldwide and is currently classified as an emerging zoonosis. Babesia microti and Babesia divergens are the most frequent etiological agents associated with human babesiosis in North America and Europe, respectively. Although the Babesia-tick system has been extensively researched, the currently available prophylactic and control methods are not efficient, and chemotherapeutic treatment is limited. Studying the molecular changes induced by the presence of Babesia in the vector will not only elucidate the strategies used by the protozoa to overcome mechanical and immune barriers, but will also contribute toward the discovery of important tick molecules that have a role in vector capacity. This review provides an overview of the identified molecules involved in Babesia-tick interactions, with an emphasis on the fundamentally important ones for pathogen acquisition and transmission.